2021
DOI: 10.3389/fcell.2021.738932
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Mitochondrial Homeostasis During Infection: A Double-Edged Sword

Abstract: Autophagy, an essential biological process that affects immunity, is a powerful tool that host cells can use to defend against infections caused by pathogenic microorganisms. Autophagy can not only initiate innate immune responses but also degrade the cellular components that provide the conditions for removing the invaders. However, hyperactivated or inhibited autophagy leads to mitochondrial dysfunction, which is harmful to the host itself and is involved in many types of diseases. Mitochondria perform the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Moreover, MiR-181b plays a protective role in KA-induced epileptic juvenile rats by attenuating autophagy and apoptosis ( Wang et al, 2019 ). Therefore, autophagy is a double-edged sword and may play different roles in different diseases and disease progress ( Wang et al, 2021 ). Our previous studies have also shown that the effect of autophagy on flap viability is controversial and needs further research ( Li et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021 ; Zhu et al, 2021 ; Lou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MiR-181b plays a protective role in KA-induced epileptic juvenile rats by attenuating autophagy and apoptosis ( Wang et al, 2019 ). Therefore, autophagy is a double-edged sword and may play different roles in different diseases and disease progress ( Wang et al, 2021 ). Our previous studies have also shown that the effect of autophagy on flap viability is controversial and needs further research ( Li et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021 ; Zhu et al, 2021 ; Lou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mitochondria have been reported to be important direct targets of Ca 2+ ; therefore, we considered whether HAP‐released Ca 2+ might help maintain mitochondrial homeostasis. Previous results have shown that mitochondrial dysfunction is closely related to cell viability 33 . The mitochondrial permeability‐transition pore (mPTP) is composed of a group of protein complexes that exist between the inner and outer membranes of mitochondria and help maintain the mitochondrial‐membrane potential (MMP) and ion balance between the inside and outside of cells 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy, as a fundamental cellular degradation mechanism in eukaryotes, is equally important in innate immune defence and pathogenic microbe clearance [ 86 , 87 ]. Bacteria induce autophagy by stimulating innate immune receptors such as TLRs.…”
Section: E Faecalis -Modulated Host Cell Responsesmentioning
confidence: 99%